Board Diversity and Financial Performance in Indonesia - Werner Ria Murhadi; Deliana Azaria; Bertha Silvia Sutedjo (Journal of Entrepreneurship and Business, 2021)
Corporate governance has attracted many researchers to examine the relationship between board characteristics and financial performance. This study aims to determine the effect of board diversity, board size, and board independence on financial performance. This research is panel data with the number of observations reaching 1,355 years of observation. Financial performance is measured using accounting-based and market-based. It was found that the presence of female directors could not provide sound financial performance, even with a woman's prudence attitude would have an impact on decreasing the company's market value. The size of the board of directors does not affect financial performance, and the large size of the board of directors will have an impact on the decline in firm value. Independent directors are also not proven to be able to improve the company's financial performance; even the tendency of companies to carelessly fulfill the provisions of the rules regarding the existence of independent directors will bring a burden to the company so that it has an impact on the decline in company value.